Comportamiento reproductivo de razas y cruces formadores de dos nuevas razas lecheras en Cuba - Ronda, R.=700 1 Tizol, G.; Fernandez, M.H.; Perez Beato, O.; Granado, A.
(En, Es)
Ilus., 18 ref.
Keywords: GANADO; RAZAS (ANIMALES); CEBU; CRUZAMIENTO; REPRODUCCION; GANADO DE LECHE; CUBA; RAZAS HOLSTEIN; REVISTA DE SALUD ANIMAL